Aplicación de una auditoria de gestión a la asociación de transporte pesado de Cotopaxi Asotrapec, ubicada en la parroquia Eloy Alfaro, del canton Latacunga, al periodo 01 de enero al 31 de diciembre 2012 - Amores Carrera, Miriam Rosalba (2015)
The research was conducted primary purpose was to establish a series of conceptual and methodological tools around effective Auditing in Asociación de Transporte Pesado de Cotopaxi. Was established as a reference material Technical - scientific knowledge in such a way to contribute to the private institution, specifically with the implementation Auditing projected in each of the departments in such a way to monitor the proper use of physical resources, financial and material handling Asociación de Transporte Pesado de Cotopaxi and efficiency leading to the fulfillment of objectives and goals for the partners and the community of Cotopaxi. The work performed is the result of many efforts in the field of research and experimental to be systematized….